MANAJEMEN LIMBAH MEDIS DI RUMAH SAKIT UMUM DAERAH ARIFIN ACHMAD PROVINSI RIAU - Iis Shalihat; Chalid Sahuri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Conducted research aims to identify and analyze medical waste management in District General Hospital Arifin Ahmad Riau Province and to determine the factors that influence the management of medical waste in District General Hospital Arifin Achmad Riau Province. Theoritical concept used is theory of environment system according to hospital by Wiku Sasmito. In this theory there are some important component in implementing environmental management system hospital. They are management support, planning, implementation, review and action. This research will used descriptive qualitative research method that analyze for in details based on the fact that comes out in field, then from interview and observation conclution can be support data presented.Research result shows that medical waste management system in District General Hospital Arifin ahmad Riau Province has been accomplished in accordance with the decision of the Health Minister of Republic Indonesia Number 1204. But it can not be said to be implemented to the fullest, because some factors that influence the implementation of medical waste management in District General Hospital Arifin ahmad Riau Province. It is operational costs and human resources.Key Words : Medical Waste, Management, Environmental Health Hospital.